Market-Induced Displacement and Its Afterlives: Lived Experiences of Loss and Resilience. Issue 3 (22nd March 2022) - Leitner, Helga; Sheppard, Eric; Colven, Emma
Abstract : We examine residents' lived experiences of market-induced displacement from informal settlements and of their afterlives in greater Jakarta—the creeping displacement of residents under pressure to sell their land rights to developers and land brokers. We interrogate four aspects of these displacees' afterlives: housing, livelihoods, rentiership, and commoning. Displacees relocate to cheaper kampungs where they can improve their housing quality. Such individualized gains are counterbalanced by social dispossession: a collective loss of the sociality and mutual aid of kampung living. These experiences are unequal, shaped by households' differentiated sociospatial positionalities, their agency and resilience, and the larger political economic context. These differentiated experiences are marked by loss, mourning, and hardship but also by the possibilities that displacees create in resettlement: efforts to maintain and re-create kampung ways of life that contest neoliberal world-class urbanism's emphasis on individualism. Conceptually, our findings question the common partitioning of displacement into voluntary and involuntary; highlight displacees' conflicting experiences and practices, taking advantage of the exchange value of land while carving out spaces of mutual aid and care; identify the importance of expanding conceptions of dispossession to encompass social and affective registers; and challenge representations of displacees as passive victims of accumulation by dispossession.